Estudantes de medicina e suas atitudes em relação à AIDS - Frauches, Diana de Oliveira (2001)
The attitudes of professional health workers towards AIDS may cause deviations in technical behavior and evaluating students' attitudes while they are still in graduate schools may allow eventual actions before practice starts, thus avoiding the establishment of negative attitudes. Based on the fact that attitudes knowledge, affection and evaluation have their origins in social life and are largely shared, and considering that the attitudes towards AIDS may be related to professional training, in addition to existing controversies about the influence of gender, a probabilistic sample of 176 medical students, arranged according to sex and insertion in the course, was selected from the first and last college years, belonging to both two medical schools located in Espirito Santo, Brazil. The Scale of Attitudes towards AIDS (AAS), developed by Shrum, Turner and Bruce, was adapted and applied to the studied population distributed in groups according to school and insertion in the course. The results were analyzed using statistics non-parametric tests. The freshmen attitudes from both medical schools were similar. In one of the schools, the tolerance increased among the last year students in comparison with the first year students, while it decreased in the other school, with growth of the variegation of the scores. The "religion" and "knowing HIV/AIDS people" variables, that were considered too, didn't produce significant differences. Also there were not significant differences between gender in the first year group. It is discussed the adjustment of AAS to be used in our environment. The proposal of further studies to know the pedagogical projects and culture of the schools were this research took place is considered, as well as the role of gender in the students' attitudes towards AIDS.